Non-aqueous electrolyte and alkali metal ion battery thereof

By using a non-aqueous electrolyte containing uracil and pennamol borate in alkali metal ion batteries, the problem of degradation of alkali metal ion batteries in high-temperature environments is solved, and high-temperature cycling and storage performance are achieved. Boost and lower battery impedance.

CN119481285AActive Publication Date: 2025-02-18ZHUHAI SMOOTHWAY ELECTRONICS MATERIALS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411712995.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-18
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Alkaline metal ion batteries In high temperature environments, alkali metal ions may evaporate from the solid surface, resulting in a decrease in the metal content inside the battery, affecting the battery performance, and may cause corrosion to the metal parts, electrolytes and separators inside the battery, shortening the use of the battery. life.

Method used

Provide a non-aqueous electrolyte solution, including electrolyte salts, non-aqueous organic solvents and additives. The additive is Compound A, which contains uracil-based structure and pennamol boric acid ester structure, which can provide protons at high potentials and form protection. The layer and induce the formation of nanoscale MF, reduce the cell impedance and improve the high-temperature cycling performance.

Benefits of technology

Effectively improve the high-temperature cycling and high-temperature storage performance of alkali metal ion batteries at a high voltage of 4.5V, while reducing the impedance of the battery and extending the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481285A_ABST
    Figure CN119481285A_ABST
Patent Text Reader

Abstract

The invention provides a non-aqueous electrolyte and an alkali metal ion battery thereof. The non-aqueous electrolyte comprises an electrolyte salt, a non-aqueous organic solvent and an additive, and the additive comprises a compound A with the following structure. According to the alkali metal ion battery, the compound A is adopted as an additive, the structure of the compound A comprises a uracil structure and a boronic acid pinacol ester structure, through the synergistic effect of the two structures, the high-temperature cycle performance and the high-temperature storage performance of the alkali metal ion battery under the high voltage of 4.5 V can be effectively improved, and meanwhile the impedance of the battery can be effectively reduced. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery electrolytes, and in particular to a non-aqueous electrolyte and an alkali metal ion battery thereof. Background Art

[0002] As a new type of battery technology, alkali metal ion batteries have received extensive attention and research in recent years. Alkali metal ion batteries, especially lithium ion batteries, are known for their high energy density and can provide long-term, high-intensity power support. At the same time, compared with traditional batteries, alkali metal ion batteries have a longer cycle life and can be charged and discharged multiple times without significantly reducing performance. With the rapid development of the electric vehicle industry, alkali metal ion batteries, as its core power source, continue to grow in market demand. However, as people's understanding of battery usage conditions continues to deepen, it is found that in alkali metal ion batteries, alkali metal ions may evaporate from the solid surface under high temperature conditions, resulting in a decrease in the metal content inside the battery, which in turn affects the performance of the battery. In addition, alkali metals are also prone to react with carbon-containing fuels or other materials to form catalytically inactive compounds, such as aluminosilicates, which will reduce the reactivity of the material and the overall performance of the battery. At the same time, at high temperatures, alkali metals may corrode metal components, electrolytes, and diaphragms inside the battery, resulting in a decrease in battery performance or even failure. This corrosion may accelerate the aging process of the battery and shorten the battery's service life. This is because the alkali metal ion battery system will undergo a series of changes under high temperature conditions. For example, when the negative electrode material is formed in the alkali metal ion battery, a SEI film will form on the surface. The SEI film will dissolve and be destroyed under high temperature conditions, thus affecting the battery's cycle performance; at the same time, when the battery is stored for a long time in a high temperature environment, the electrolyte will volatilize or reduce and decompose, causing the battery "flatulence" problem. Therefore, when facing high temperature conditions, the design of the non-aqueous electrolyte of the alkali metal ion battery must take into account the compatibility between the positive and negative electrode materials and the electrolyte of the alkali metal ion battery under high temperature conditions, so as to reduce the probability of the electrolyte reacting with the positive and negative electrodes and improve the stability of the SEI film. At present, some researchers in the industry can solve the battery's flatulence problem to a certain extent by adding a certain amount of special additives, but it seriously affects the high temperature cycle performance of the alkali metal ion battery. At the same time, some researchers can build a strong SEI film on the cathode and anode by adding special additives, thereby significantly improving the high temperature and high pressure performance of the soft-pack full battery, but due to its large interface impedance, it affects the battery's cycle performance. Therefore, developing new non-aqueous electrolytes to effectively balance the high-temperature cycle performance and high-temperature storage performance of alkali metal ion batteries is a key issue that needs to be addressed in the further development of alkali metal ion batteries. Summary of the invention

[0003] The object of the present invention is to provide a non-aqueous electrolyte and an alkali metal ion battery thereof, wherein the non-aqueous electrolyte can effectively improve the high temperature cycle performance and high temperature storage performance of the alkali metal ion battery at a high voltage of 4.5V, and can effectively reduce the impedance of the battery.

[0004] To achieve the above object, the present invention provides a non-aqueous electrolyte, including an electrolyte salt, a non-aqueous organic solvent and an additive, wherein the additive includes a compound A having the following structure:

[0005]

[0006] Compound A (CAS: 269410-01-7).

[0007] Compared with the prior art, the additive of the non-aqueous electrolyte of the present invention includes compound A, which contains uracil structure and boric acid pinacol ester structure. The methyl group connected to the ring of compound A can provide protons at high potential to protect the non-aqueous electrolyte so that it can withstand high voltage; the BO bond in the boric acid pinacol ester structure is easy to break in the formation stage, and after the BO bond is broken, a protective layer can be preferentially formed on the surface of the positive electrode material, and at the same time, nano-scale MF (M refers to Li, Na or K) can be induced to form, so that the battery has a higher capacity retention rate, and its film-forming property can also reduce the generation of the positive electrode salt rock phase, and has the effect of reducing impedance in the non-aqueous electrolyte system, and improves the high-temperature cycle performance of the alkali metal ion battery. At the same time, the N-heterocyclic structure in the uracil structure can form a film on the surface of the positive and negative electrode sheets and construct a stable solid electrolyte layer interface in the formation stage. The solid electrolyte layer interface is not easy to dissolve even under high temperature conditions, thereby extending the battery cycle life. Therefore, the non-aqueous electrolyte of the present invention can improve the storage performance and cycle performance of alkali metal ion batteries under high temperature conditions, and can effectively reduce its impedance.

[0008] As a preferred technical solution, the mass percentage of the additive in the non-aqueous electrolyte is 0.5% to 1.0%. Specifically, the mass percentage of the additive in the non-aqueous electrolyte is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%.

[0009] As a preferred technical solution, the electrolyte salt of the present invention is selected from lithium salt, sodium salt or potassium salt.

[0010] As a preferred technical solution, the lithium salt is selected from lithium hexafluorophosphate (LiPF 6 ), lithium perchlorate (LiClO 4 ), lithium tetrafluoroborate (LiBF 4 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium methanesulfonate (LiCH 3 SO3 ), lithium trifluoromethanesulfonate (LiCF 3 SO 3 ), lithium fluorosulfonate (LiSO 2 F), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium difluorophosphate (LiPO 2 F 2 ), lithium difluorobis(oxalyl)phosphate (LiDFAP), lithium bis(fluorosulfonyl)imide (LiFSI) and at least one of lower aliphatic lithium carboxylate.

[0011] The sodium salt is selected from sodium hexafluorophosphate (NaPF 6 ), sodium perchlorate (NaClO 4 ), sodium tetrafluoroborate (NaBF 4 ), sodium bis(oxalatoborate) (NaBOB), sodium trifluoromethanesulfonate (NaCF 3 SO 3 ) and sodium bis(trifluoromethanesulfonyl)imide (NaTFSI).

[0012] The potassium salt is selected from potassium hexafluorophosphate (KPF 6 ), potassium tetrafluoroborate (KBF 4 ), potassium perchlorate (KClO 4 ), potassium hexafluoroarsenate (KAsF 6 ), potassium hexafluoroantimonate (KSbF 6 ), potassium difluorophosphate (KPF 2 O 2 )、4,5-dicyano-2-trifluoromethylimidazolium potassium (KDTI), bis(oxalyl)borate potassium (KBOB), difluorooxalyl borate potassium (KDFOB), bis(fluorosulfonyl)imide potassium (KFSI), KN(SO 2 RF) 2 、KN(SO 2 F)(SO 2 RF), potassium nitrate (KNO 3 ) and potassium chloride (KCl), wherein RF = C n F 2n+1 , n is an integer from 1 to 10.

[0013] As a preferred technical solution, the mass percentage of the electrolyte salt of the present invention in the non-aqueous electrolyte is 5% to 20%. Specifically, the mass percentage of the electrolyte salt of the present invention in the non-aqueous electrolyte is 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 18%, 20%.

[0014] As a preferred technical solution, the non-aqueous organic solvent of the present invention is selected from at least one of chain carbonates, cyclic carbonates, carboxylates and lactones.

[0015] As a preferred technical solution, the chain carbonate may be at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), propyl methyl carbonate (PMC), and ethyl propyl carbonate (PEC); the cyclic carbonate may be at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), and pentylene carbonate; the carboxylic acid ester may be at least one of methyl acetate (MA), ethyl acetate (EA), propyl acetate, methyl propionate, ethyl propionate (EP), and propyl propionate (PP); the lactone may be at least one of γ-butyrolactone (GBL), γ-valerolactone (GVL), γ-caprolactone, δ-valerolactone (DVL), and ε-caprolactone.

[0016] On the other hand, the present invention provides an alkali metal ion battery, which includes a positive electrode and a negative electrode, and also includes the aforementioned non-aqueous electrolyte, and the maximum charging voltage of the alkali metal ion battery is 4.5V.

[0017] As a preferred technical solution, the positive electrode of the present invention includes a positive electrode active material, and the positive electrode active material is selected from at least one of metal oxides and polyanion-type compounds.

[0018] Specifically, the metal oxide includes lithium cobaltate, lithium iron phosphate, nickel cobalt manganese oxide, sodium nickel iron manganese oxide, or nickel cobalt aluminum oxide. The lithium cobaltate may be lithium cobaltate or lithium cobaltate modified by doping and coating. The lithium iron phosphate may be lithium iron phosphate or lithium iron phosphate modified by doping and coating. The chemical formula of the nickel cobalt manganese oxide is LiNi x Co y Mn z M (1-x-y-z) O 2 , and the chemical formula of the nickel cobalt aluminum oxide is LiNi x Co y Al z N (1-x-y-z) O 2 , where M is at least one of Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V, and Ti, N is at least one of Mn, Mg, Cu, Zn, Sn, B, Ga, Cr, Sr, V, and Ti, 0≤x<1, 0<y<1, 0<z<1, and x + y + z≤1. The chemical formula of the polyanion-type compound is R x N y (XO z ) n, wherein R is independently selected from one of Li, Na and K, N is independently selected from at least one of Fe, Mn, Ni, Cu and V, X is independently selected from one of S, P, Si, Mo and As, 1≤x≤4, 1≤y≤3, 1≤n≤3, 1≤z≤4.

[0019] Furthermore, the negative electrode of the present invention comprises a negative electrode active material, and the negative electrode active material is selected from at least one of artificial graphite, hard carbon, natural graphite and mesophase microspheres. DETAILED DESCRIPTION

[0020] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0021] Example 1

[0022] (1) Preparation of non-aqueous electrolyte

[0023] In an argon atmosphere and in a vacuum glove box with a moisture content of <1ppm, ethylene carbonate (EC) and propyl propionate (PP) were mixed in a weight ratio of EC:PP=1:4 to prepare 87g of a non-aqueous organic solvent, to which 0.5g of compound A was added respectively, dissolved and stirred thoroughly, and then 12.5g of LiPF6 was added and mixed evenly to obtain a non-aqueous electrolyte.

[0024] (2) Preparation of positive electrode

[0025] LiCoO 2 , adhesive PVDF and conductive agent SuperP are evenly mixed in a mass ratio of 95:1:4 to form an alkali metal ion battery positive electrode slurry with a certain viscosity. The mixed slurry is coated on both sides of an aluminum foil, and then dried and rolled to obtain a positive electrode sheet.

[0026] (3) Preparation of diaphragm

[0027] Polyethylene (PE) with a thickness of about 15 μm was used as the isolation film.

[0028] (4) Preparation of negative electrode

[0029] The negative electrode graphite material, the adhesive PVDF and the conductive agent SuperP are mixed evenly in a mass ratio of 90:2:8 to prepare an alkali metal ion battery negative electrode slurry with a certain viscosity. The mixed slurry is coated on both sides of a copper foil, and then dried and rolled to obtain a negative electrode sheet.

[0030] (5) Preparation of alkali metal ion batteries

[0031] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, and then stacked as needed. After the tabs are welded, they are placed in the aluminum-plastic film of the battery outer packaging, and the prepared non-aqueous electrolyte is injected into the dried bare battery cell, and vacuum packaging, static, formation (0.05C constant current charging to 3.6V, and then 0.1C constant current charging to 3.9V), shaping, capacity testing and other processes are carried out successively, and finally a 2Ah soft-pack alkali metal ion battery is obtained.

[0032] Embodiments 2 to 5

[0033] The alkali metal ion batteries of Examples 2 to 5 differ from those of Example 1 only in the non-aqueous electrolytes, and the rest are the same. The formulas of the non-aqueous electrolytes of Examples 2 to 5 are shown in Table 1.

[0034] Example 6

[0035] The difference between Example 6 and Example 1 is that the preparation of the positive electrode sheet is different and the non-aqueous electrolyte is different, and the rest is the same. The preparation of the positive electrode sheet of Example 6 includes: preparing the ternary material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 , adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 95:1:4 to form a sodium ion battery positive electrode slurry with a certain viscosity. The mixed slurry is coated on both sides of an aluminum foil, and then dried and rolled to obtain a positive electrode sheet. The formula of the non-aqueous electrolyte of Example 6 is shown in Table 1.

[0036] Example 7

[0037] The difference between Example 7 and Example 1 is that the preparation of the positive electrode sheet is different and the non-aqueous electrolyte is different, and the rest is the same. The preparation of the positive electrode sheet of Example 7 includes: grinding the K 3 V 2 (PO 4 ) 3 , adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 95:1:4 to form a positive electrode slurry for a sodium ion battery with a certain viscosity, and the mixed slurry is coated on both sides of an aluminum foil, and then dried and rolled to obtain a positive electrode sheet. The formula of the non-aqueous electrolyte of Example 7 is shown in Table 1.

[0038] Comparative Examples 1 to 3

[0039] The difference between Comparative Examples 1 to 3 and Example 1 is the non-aqueous electrolyte, and the rest is the same. The formula of the non-aqueous electrolyte of Comparative Example 1 is shown in Table 1.

[0040] Comparative Example 4

[0041] The difference between Comparative Example 4 and Example 6 is the non-aqueous electrolyte, and the rest are the same. The formula of the non-aqueous electrolyte of Comparative Example 4 is shown in Table 1.

[0042] Comparative Example 5

[0043] The difference between Comparative Example 5 and Example 7 is the non-aqueous electrolyte, and the rest are the same. The formula of the non-aqueous electrolyte of Comparative Example 5 is shown in Table 1.

[0044] Table 1 Non-aqueous electrolyte components of various examples and comparative examples

[0045]

[0046]

[0047] In Table 1, the structures of Compound 1 and Compound 2 are shown below:

[0048]

[0049] Compound 1 (CAS: 66-22-8) Compound 2 (CAS: 193978-23-3)

[0050] The electrochemical performance of the alkali metal ion batteries prepared in Examples 1 to 7 and Comparative Examples 1 to 5 was tested. The specific test conditions are as follows. The test results are shown in Table 2.

[0051] High temperature cycle performance test

[0052] The alkali metal ion batteries of Examples 1 to 7 and Comparative Examples 1 to 5 were charged and discharged at 2.0C / 1.0C once at 45°C (the battery discharge capacity is C0), with an upper limit voltage of 4.5V, and then charged and discharged at 2.0C / 1.0C for 300 cycles at 45°C (the battery discharge capacity is C1), and the capacity retention rate was calculated according to the following formula:

[0053] Capacity retention rate = (C1 / C0)*100%

[0054] High temperature storage performance test

[0055] The alkali metal ion batteries of Examples 1 to 7 and Comparative Examples 1 to 5 were charged and discharged at 0.5C / 0.5C at 25°C, with an upper voltage limit of 4.5V, and then the batteries were charged to full power at 0.5C at room temperature, with an upper voltage limit of 4.5V, and the battery thickness was recorded as V0. After the alkali metal ion batteries were stored at 85°C for 24 hours, the battery thickness was measured as V1, and the thickness expansion rate was calculated according to the following formula:

[0056] Thickness expansion rate = (V1-V0) / V0*100%

[0057] High temperature storage internal resistance change rate test

[0058] The alkali metal ion batteries of Examples 1 to 7 and Comparative Examples 1 to 5 were subjected to 5 charge-discharge cycle tests at room temperature at a charge-discharge rate of 0.5C / 0.5C, with an upper limit voltage of 4.5V. Finally, they were charged to a fully charged state at a rate of 0.5C, with an upper limit voltage of 4.5V. The internal resistance of the alkali metal ion battery was recorded as T0. The fully charged alkali metal ion battery was stored at 60°C for 15 days, and the internal resistance of the sodium ion battery was recorded as T. The internal resistance change rate was calculated according to the following formula:

[0059] Internal resistance change rate = (T-T0) / T0*100%

[0060] Table 2 Performance test results of various embodiments and comparative examples

[0061]

[0062] As shown in the test results of Table 2, the high-temperature cycle performance and high-temperature storage performance of Examples 1 to 7 and alkali metal ion batteries are better than those of Comparative Examples 1 to 5. This may be because the non-aqueous electrolyte of the present invention includes compound A, which contains uracil structures and boric acid pinacol ester structures. The methyl group connected to the ring of compound A can provide protons at high potentials to protect the non-aqueous electrolyte to make it resistant to high voltage; the BO bond in its boric acid pinacol ester structure is easily broken during the formation stage, and after the BO bond is broken, a protective layer can be preferentially formed on the surface of the positive electrode material, and at the same time, nano-scale MF (M refers to Li, Na or K) can be induced to form, so that the battery has a higher capacity retention rate, and its film-forming property can also reduce the formation of the positive electrode salt rock phase, and has an impedance-reducing effect in the non-aqueous electrolyte system, thereby improving the high-temperature cycle performance of the alkali metal ion battery. At the same time, the N-heterocyclic structure in the uracil structure can form a film on the surface of the positive and negative electrode sheets and construct a stable solid electrolyte layer interface during the formation stage. The solid electrolyte layer interface is not easily dissolved even under high temperature conditions, thereby extending the battery cycle life. Therefore, the non-aqueous electrolyte of the present invention can improve the storage performance and cycle performance of alkali metal ion batteries under high temperature conditions and can effectively reduce their impedance.

[0063] Comparing the performance data of Example 1 with the performance data of Comparative Examples 1 and 2, it can be seen that the high temperature cycle performance, high temperature storage performance and internal resistance growth rate of Comparative Example 2 are all worse than those of Example 1 but better than those of Comparative Example 1. This may be because Compound 1 in Comparative Example 2 can react at the cathode and anode in preference to solvent molecules, and the inhibitory effect on the decomposition of electrolyte solvent is most obvious. However, since the molecular structure of uracil contains two carbonyl groups (C=O) and two nitrogen atoms, the carbonyl group has a strong electron-withdrawing ability, which may lead to uneven distribution of electron clouds around the molecule, affecting its interaction with ions in the electrolyte, and is not conducive to the migration of ions, thereby increasing impedance. Although the nitrogen atoms in uracil can participate in certain coordination effects, due to the chemical environment and position in which they are located, they may not be able to effectively form a stable coordination structure with lithium ions that is conducive to ion transmission, which hinders ion transmission and increases impedance. At the same time, the degree of conjugation of uracil molecules is relatively low, and the degree of delocalization of electrons in the molecule is limited, which may limit its ability to accept and transfer electrons in the electrolyte, and the promotion effect on ion conduction is not obvious, resulting in increased impedance. In summary, the special structure of uracil makes it difficult to effectively promote ion transport in the electrolyte, thus showing a large impedance, which in turn leads to limited performance improvement in high-temperature cycle performance and high-temperature storage performance. Comparing the performance data of Example 1 with the performance data of Comparative Example 1 and Comparative Example 3, it can be seen that the high-temperature cycle performance and high-temperature storage performance of Comparative Example 3 are worse than those of Example 1 but better than those of Comparative Example 1. This may be because Compound 2 containing a thiophene-2-pinacol borate structure is easy to undergo an oxidative electropolymerization reaction on the surface of the positive electrode to generate a sulfur-containing interface film with low impedance, which can improve the cycle performance of lithium-ion batteries. However, since the double bonds it contains are easy to open-ring polymerize, the interface impedance is large at high temperatures, resulting in deterioration of high-temperature cycle and storage performance, so its role in improving the high-temperature storage and high-temperature cycle of alkali metal ion batteries and reducing their impedance is also relatively limited.

[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A non-aqueous electrolyte comprising an electrolyte salt, a non-aqueous organic solvent and an additive, characterized in that: The additive includes a compound A having the following structure:

2. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage of the additive in the non-aqueous electrolyte is 0.5% to 2.0%.

3. The non-aqueous electrolyte according to claim 1, characterized in that The electrolyte salt is selected from lithium salt, sodium salt or potassium salt.

4. The non-aqueous electrolyte according to claim 3, characterized in that The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium methanesulfonate, lithium trifluoromethylsulfonate, lithium fluorosulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorophosphate, lithium difluorobis(oxalatophosphate), lithium diphosphate and lithium lower aliphatic carboxylate, and the sodium salt is selected from sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(oxalatoborate), trifluoromethylsulfonate The potassium salt is selected from at least one of sodium hexafluorophosphate, potassium tetrafluoroborate, potassium perchlorate, potassium hexafluoroarsenate, potassium hexafluoroantimonate, potassium difluorophosphate, 4,5-dicyano-2-trifluoromethylimidazolium potassium, potassium bisoxalate borate, potassium difluorooxalate borate, potassium bis(fluorosulfonyl)imide, KN(SO2RF)2, KN(SO2F)(SO2RF), potassium nitrate and potassium chloride.

5. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage of the electrolyte salt in the non-aqueous electrolyte is 5% to 20%.

6. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous organic solvent is selected from at least one of chain carbonates, cyclic carbonates, carboxylates and lactones.

7. The non-aqueous electrolyte according to claim 6, characterized in that The linear carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate and ethyl propyl carbonate; the cyclic carbonate is selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate and pentylene carbonate; the carboxylic acid ester is selected from at least one of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate and propyl propionate; and the lactone is selected from at least one of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone.

8. An alkali metal ion battery comprising a positive electrode and a negative electrode, characterized in that: It also comprises the non-aqueous electrolyte according to any one of claims 1 to 7, and the maximum charging voltage of the alkali metal ion battery is 4.5V.

9. The alkali metal ion battery according to claim 8, characterized in that: The positive electrode includes a positive electrode active material, and the positive electrode active material is selected from at least one of a metal oxide and a polyanionic compound.

10. The alkali metal ion battery according to claim 8, characterized in that: The negative electrode comprises a negative electrode active material, and the negative electrode active material is selected from at least one of artificial graphite, natural graphite, hard carbon and mesophase microspheres.

Citation Information

Patent Citations

  • Lithium secondary battery electrolyte and lithium secondary battery

    CN108417894A

  • Electrolyte and secondary battery

    CN116315078A

  • Non-aqueous electrolyte and lithium ion battery thereof

    CN116845358A

  • Electrolyte and lithium ion battery

    CN117175014A

  • Lithium ion battery non-aqueous electrolyte and lithium ion battery

    CN117747947A